Diseño de un Sistema de Gestión Ambiental en el Campus CEASA de la Universidad Técnica de Cotopaxi en el período 2020 – 2021 - Moyano Toaquiza, Andrea Carolina (2021)
The objective of this research report is to design an Environmental Management System at CEASA Campus, a balance between the environment, society and economy are essential to reimburse present needs, without risking future generations, these three pillars are essential to meet the objective of sustainability. On the other hand, a field methodology was established in order to give an answer to the proposed problem, this research is based on check-list report using established parameters on ISO 14001-2015 standard, which allow us an initial evaluation of all different departments located at CEASA Campus, therefore, the bibliographic documentary methodology helps to get knowledges through the collection, analysis, and understanding of information from reliable documentary sources. In addition, one of the techniques that was used in this researching is, direct observation, this method helped to evaluate the processes carried out in each of the departments within of this investigation. Through the qualitative modality, it is possible to get a specific data using a survey as strategy, which allows an evaluation of all departments at the campus, and also a personal interview is made to all professors who works at the campus, the goal is to recognize the different conformities and non-conformities in each department. In addition, the success of an environmental management system is focused on the concept of PDCA CYCLE: plan, do, check, act, using this process correctly the institution will improve its environmental performance and as a consequence, a better environment quality, ISO 140001-2015 international standard gets environmental results, joining those results with an environmental policy of the institution, the results influence in a correct way. Finally, it is concluded that the initial environmental diagnosis made to CAREN Faculty provided us information regarding the absence of an environmental management system, because of lack of protocols to eliminate wastes generated in their activities. And also, some critical points were identified during this research, therefore many improvements opportunities are made.